Immunity and Community in Esposito, Derrida and Agamben - Rosàs Tosas, Mar (Revista de Filosofía, 2022)
Roberto Esposito (1998; 2002; 2008) examines how immunological apparatuses originally designed to protect communities end up undermining communities. This paper explores comparatively his view on the interplay between community and immunity with Giorgio Agamben’s and Jacques Derrida’s, although in their works these notions appear under other labels. Beyond pointing out their similarities, the paper concludes by analyzing what, in our view, constitute the raison d’être of their ultimate and irreconcilable differences: Agamben’s approach is antinomic, while Derrida’s is aporetic and Esposito’s is rather dialectical.